Metal–organic frameworks constructed from an [MS4Cux]x−2 (M = W, Mo) unit: isomerization of the cluster unit induced by temperature. Issue 38 (23rd September 2021) - Meng, Mei-Mei; Xi, Ji-Ming; Wang, Li-Fei; Zhu, Rui; Zhang, Rui; Lu, Zhen-Zhong; Zheng, He-Gen; Huang, Wei
Abstract : Two MOFs based on [WS4 Cu4 ] 2+ or unprecedented [WS4 Cu6 ] 4+ ·I − ·[WS4 Cu6 ] 4+, and a MOF based on [MoS4 Cu4 ] 2+ with 9, 10-di(pyridin-4-yl)anthracene were obtained. Temperature was important for the isomerization of [WS4 Cu x ] x −2 in the formation of two MOFs based on [WS4 Cu x ] x −2 . Abstract : An [MS4 Cu x ] x −2 cluster unit (M = W, Mo, x = 1, 2, …6) is a kind of heterothiometallic unit of versatile connectivities and geometries for building metal–organic frameworks (MOFs) of intriguing structures and properties. We here report two MOFs based on the [WS4 Cu x ] x −2 unit and a MOF based on the [MoS4 Cu x ] x −2 unit with 9, 10-di(pyridin-4-yl)anthracene (dpa). 1 contains penta-nuclear [WS4 Cu4 ] 2+ units, which act as tetrahedral nodes and are linked by dpa ligands into a 5-fold interpenetrated diamondoid network. 2 contains an unprecedented [WS4 Cu6 ] 4+ ·I − ·[WS4 Cu6 ] 4+ unit where two hepta-nuclear [WS4 Cu6 ] 4+ units are bridged by an I − ion, which acts as a 7-connector node, leading to a 3D network with the rare hxg-d topology. 3 is built from penta-nuclear [MoS4 Cu4 ] 2+ units and dpa ligands and is isostructural to 1 . The structural difference between 1 and 2 should come from the isomerization of the [WS4 Cu x ] x −2 unit in the synthesis processes, and we found that temperature was much more important than other factors, such as solvent, the halide anion of the Cu I salt and the ratio of [NH4 ]2 WS4 to Cu I salt, for the isomerization of the [WS4 Cu x ] x −2 unit in the formation of 1 and 2 .